Pengaruh Aktivitas Belajar Siswa Pada Pembelajaran Creative Problem Solving Berbasis Media Quizizz Terhadap Kemampuan Pemecahan Masalah Matematika - Dea Mutiara Amelia; Mochamad Abdul Basir (Pendidikan Matematika FKIP Universitas Mataram, 2026)
This study aims to describe the effect of student learning activities through Quizizz-based Creative Problem Solving (CPS) learning on mathematical problem-solving abilities. The background of this study is based on the low mathematical problem-solving abilities caused by students' learning activities that have not been optimally facilitated. This study uses a quantitative approach with a correlational non-experimental design. The research subjects consisted of 32 ninth-grade students of SMP NU Al Ma'ruf Kudus. The research instruments used were a student learning activity questionnaire and a mathematical problem-solving ability test. The data were analyzed using a simple linear regression test. The results of the regression test showed that students' learning activities significantly influenced their mathematical problem-solving abilities. The average post-test score of students was 83.2031 and was included in the high category, while the questionnaire results showed that students' learning activities were in the active category. These findings indicate that Quizizz-based CPS learning has a positive effect on improving mathematical problem-solving abilities because it creates interactive learning and encourages active student involvement. Based on these findings, Quizizz-based CPS learning is recommended to be implemented as an alternative mathematics learning to improve students' learning activities and mathematical problem-solving abilities.